Ketimpangan Perlindungan Hukum Pidana dalam Penanganan Kasus Kekerasan terhadap Pekerja Seks - Manalu, Triwandani; Dumillah, Dewic Sri Ratnaning (HUMANIORUM, 2024)
This research addresses the legal inequality in handling cases of violence against sex workers, focusing on the gap in criminal law protection. The study explores the social stigma, patriarchal culture, and legal biases that contribute to this issue. It also examines the inadequate regulations and the lack of gender equality awareness that further hinder justice for sex workers. The findings suggest that these factors perpetuate victim-blaming and prevent sex workers from accessing legal protection and support.The research utilizes a qualitative method with a normative legal approach, analyzing regulations and the interpretation of legal norms. Primary and secondary data sources were collected through comprehensive library research.The study reveals that social stigma and gender biases significantly affect the justice system's response to violence against sex workers, with many cases going unaddressed. The lack of specific legal protections for sex workers exacerbates the inequality in their legal treatment. Furthermore, limited resources and knowledge among law enforcement officials hinder effective handling of such cases. The research concludes that a comprehensive approach involving regulatory reform and social awareness is essential to address this issue.